The Effect of Play Learning Method on School Maturity in the Control and Experiment Class of Raudhatul Athfal - Budianti, Yusnaili; Arsyad, Junaidi; Aceh, Yusna (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
The purpose of this study was to investigate the impact of play and creativity learning methods on school maturity in Raudhatul Atfhal children in Gunungsitoli City. This study employed a quasi-experimental methodology. This method was chosen because the treatment class included both the learning class using the play method and the learning class using the formal method and the characteristics of the children being controlled were creativity, using Population and Research Samples. The study's findings indicate that learning methods have a positive and significant influence on children's school maturity. This can be seen in the difference in average school maturity test results of children taught by the play learning method as a whole, both in the group of children with high creativity and low creativity, which is higher than the difference in average school maturity test results of children taught by formal learning methods. Thus, to increase the maturity of children's schools, the method of learning through play is more effectively applied in learning at Raudhatul Atfhal.